Is Management Education in Sync with Industry Requirement? - Patil, Krishnaji S. (Journal of Engineering Education Transformations, 2016)
The purpose of education is multi-fold. First is to train students to be employable after completion of education. This employment should be full in that the complete his complete financial requirements should be fulfilled. The second is to equip with such sufficient knowledge that they can further the knowledge in their field by engaging in research activities along with teaching. In the process their financial needs also should be fully met. In the present management education, the main emphasis is on theory. Little is done to expose the students to real life situation. This results in producing graduates who may be well-versed in theoretical base of management with little exposure to practical aspects. So leaving out a few exceptions majority of management graduates are unemployable. So we have a peculiar situation having plenty with no use. This paper attempts analyse the utility of present-day management education and suggest ways and means of making it purposive and make it synchronous with industry and society requirements.